Muon (g − 2) and flavor puzzles in the U(1)X-gauged leptoquark model - Wang, Xin (The journal of high energy physics, 2022)
A bstract We present an economical model where an S 1 leptoquark and an anomaly-free U(1) X gauge symmetry with X = B 3 − 2 L μ / 3 − L τ / 3 are introduced, to account for the muon anomalous magnetic moment a μ ≡ ( g μ − 2) and flavor puzzles including R K ∗ and R D ∗ anomalies together with quark and lepton flavor mixing. The Z ′ gauge boson associated with the U(1) X symmetry is responsible for the R K ∗ anomaly. Meanwhile, the specific flavor mixing patterns of quarks and leptons can be generated after the spontaneous breakdown of the U(1) X gauge symmetry via the Froggatt-Nielsen mechanism. The S 1 leptoquark which is also charged under the U(1) X gauge symmetry can simultaneously explain the latest muon ( g − 2) result and the R D ∗ anomaly. In addition, we also discuss several other experimental constraints on our model.